Analysis of Tourism Carrying Capacity and Land Carrying Capacity in Nyama Hamlet, Moa Island, Southwest Maluku Regency - Grano V kayapa; Rita Parmawati; Dini Atikawati (Postgraduate, University of Mataram, 2026)
Gerdarsi Beach is an undeveloped beach in Nyama Hamlet, Southwest Maluku Island, Indonesia. It features a 1.5 km long white sandy shoreline, coral reefs 100-300 m offshore, lowland topography (0-5 m above sea level), savannah vegetation, and minimal basic infrastructure. With only one manager, this beach serves as a representative case study for research on carrying capacity in remote destinations in Indonesia. The purpose of this study is to calculate tourism carrying capacity (physical carrying capacity, real carrying capacity, and effective carrying capacity). Carrying capacity is used to calculate land capacity, population size, and space per person. A quantitative method was used, with calculations based on Douglass, Vandelli, and Muhammad using Microsoft Excel to calculate the tourism carrying capacity. The research results show that the current tourist arrival rate is 302 people per day, while the physical carrying capacity (PCC) reaches 2,966,860 people per day. The actual carrying capacity (RCC) and effective carrying capacity (ECC) have been exceeded by 302 visits per day, necessitating control through visitor restrictions. The land carrying capacity, with an area of ​​17.20 km² and a population of 935, is 1.83 ha per person. This study concludes that PCC is still feasible for development, while RCC and ECC need to be remanaged or controlled. The land carrying capacity, with an area of ​​17.20 km² and a population of 935, is 1.83 ha per person. This study concludes that PCC is still feasible for development, while RCC and ECC need to be remanaged or controlled. The contribution of this research is to provide an integrated management model for PCC, RCC, ECC, and land carrying capacity in the Nyama Hamlet residential area, as well as to provide scientific data for sustainable management planning at the local and international levels.